Snapdragons: the animal party - Morgan, Michaela; Finlay, Lizzie (Oxford University Press Oxford, 2004)
When a girl organises a fancy-dress party, she asks the children if they can make animal noises to match their costumes. Then she invites them to the party where they meet the real animals